Penspesiesan ion-ion ferum dengan resin poli(asid hidroksamik) - Wan Yunus, Wan Md Zin; Haron, Md. Jelas (Penerbit Universiti Kebangsaan Malaysia, 1996)
Poly(hydroxamic acid) ion exchange resin was evaluated for speciation of iron(II) and iron(III) ions. Distribution coefficients indicate that the resin is more selective towards iron(III) ion. Column extractions show that iron(III) ion is quantatively extracted from sulfuric acid solutions at concentrations of between 0.01 to 0.00lM but only 2% or less of iron(II) ion is retained under these conditions. Further studies show that these two ions can be separated and their separations are not affected by the presence of nickel, zinc, copper, calcium, chloride, bromide, nitrate and sulphate.